Mysterious Bargaining - Dan Usher (Queen's University, Department of Economics, 2001)
Economists do not understand how bargains are struck. A bargain is the sharing of a pie between two or more people who are collectively entitled to the pie but cannot appropriate it until they agree how large each person's slice is to be. We know that people do strike bargains and that civilized life could not proceed otherwise. We do not know how the required agreement is reached. Theorists have solved the bargaining problem, but only by the imposition of strong, artificial and unrealistic constraints. Trusting that the existence of some complex solution has been demonstrated, applied economists are content to postulate a simple one: that bargainers split the difference in actual disputes. This paper begins with examples of imposed bargaining solutions in politics and corporation finance. There follows a critical examination of the principal bargaining theories - based on notions of fairness or of imposed bargaining procedures - with emphasis on the fragility of their assumptions and on their susceptibility to threats and blackmail. The paper closes with a brief discussion of connections among theories of bargaining, rent-seeking and conflict.
Keywords: C7; 330; Bargaining; Fairness